Subpopulações de linfócitos em pacientes com formas reacionais de hanseníase atendidos no Centro de Dermatologia D. Libânia, em Fortaleza - Ce - Montezuma, Bárbara Osório Xavier (2011)
Leprosy is a granulomatosic chronic disease which is highly infectious but has low pathogeticity and is caused by the Mycobacterium leprae. This study aims at describing the lymphocytes subsets T total (CD3+), T helper (CD4+), T cytotoxic (CD8+), T CD4+CD8+, B (CD19+), natural killers-NK (CD3- CD16+ CD56+) and T natural killers -NKT (CD3+ CD16+ CD56+) in patients with leprosy reactions, compare them with the ones who did not show leprosy reactions and differentiate the alterations of lymphocyte between the patients with type 1 and type 2 reactions. We used flow cytometry to quantify the lymphocytes and the Graph Pad Prism 4.0 program for the statistical analysis. We formed subgroups according to the presence (R+) or not (R-) of reaction and the period in which the patient was concerning to the multidrug therapy (MDT): before (An), during (Du) and after (Ap). We did not observe any significant differences in the lymphocytes between the groups with and without reaction, but we observed a decreased NK count in the R+/Ap subgroup when compared to the R-/Ap (p= 0,0228) and a decreased NKT count in the R-/Ap subgroup when compared to R-/An X (p< 0,05). Regarding to the reactional forms (type 1, type 2 or mixed), we observed an increase of the CD19+ cell population in the mixed forms.